A Development of E-Module Learning Media based on SETS (Science, Environment, Technology, and Society) on Sound Wave Material - Elistiana, Veny; Novita, Nanda; Ginting, Fajrul Wahdi (MANDAILING GLOBAL EDUKASIA, 2024)
Electronic Module (E-Module) is a type of interactive multimedia teaching material presented electronically which contains images, text and videos arranged systematically which are useful for forming a more creative learning process. The learning process at State Islamic Senior High School of 3 North Aceh currently still uses the conventional model and teachers have never conducted learning using interactive learning media such as e-modules. This research aims to determine the feasibility and practicality of SETS-based e-module learning media products as media that make it easier for students to learn sound wave material for class XI at the State Islamic Senior High School of 3 North Aceh. This development research method refers to Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). The research subjects were physics subject teachers at the State Islamic Senior High School of 3 North Aceh and students in class XI MIA 3 with a total of 16 students. The results obtained are: 1) The results of validation by the media obtained a percentage of 85.23% in the